Pengaruh Umur Starter terhadap Rendaman Nata Nira Aren - Andi, Taskirah (bionature, 2011)
Aren (Arenga pinnata, Merr) was one type of palm tree of the family was well known area of the tropics because of various benefits. Starting from the root, stem, bark, leaves, fruits, fibers up to the treetops. The variables in this study were age starter as the independent variable and the yield of sugar as a variable independent. Design used a completely randomized design (CRD) consisting of three treatments with three replications. Each repeat unit there were 3 observations. So that the overall number of observation units 3 x 3 x 3 = 27. The treatment used in this study, namely: A1 = Age starter 4 days, A2 = Age 6 day starter, starter A3 = Age 8 days. The parameters measured in this study is the yield produced nata, nata yield measured by weighing the first nata formed have drained for 1 hour and then divided by the volume of juice used. Data obtained with the variation (F test) to see the effect on the level sig Î± = 0.01. When the results showed a treatment effect of the test followed by LSD Î± = 0.01. The results showed that age affects the formation of nata starter.